1985
DOI: 10.1161/01.res.57.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Localization of beta 1- and beta 2-adrenergic receptors in rat kidney by autoradiography.

Abstract: beta-Adrenergic receptor subtypes were localized and differentiated in rat kidney slices by in vitro autoradiography using the nonselective beta-antagonist [125I]iodocyanopindolol in the presence of the selective agents betaxolol (beta 1) and zinterol (beta 2). [125I]Iodocyanopindolol binding to kidney sections in the presence of these agents could be differentiated into high- and low-affinity components as predicted by the subtype selectivity of the compounds. Autoradiography revealed that: beta-adrenergic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
1
6
1
Order By: Relevance
“…Summers et al demonstrated that those receptors distributing in the distal nephron are mainly of the/?1 subtype, while both/I1 and 82 subtypes of receptors are present in glomeruli [8], data largely in agreement with our present results except for the lack of proximal 82 receptors. In contrast Healy et al have reported that those receptors distributing in glome~li are mainly of the pl subtype whilst the /I2 subtype of receptors are distributed in medullary tubules [22]. Although the reasons for the conflicting data reported in the literature, as well as some disagreements of our present results with others, may not be identified unequivocally, the problem of cross-reactivity of pharmacological agents should always be considered.…”
Section: Rt-pcr Of Intronless Genes Has Been Reported Bycontrasting
confidence: 96%
See 1 more Smart Citation
“…Summers et al demonstrated that those receptors distributing in the distal nephron are mainly of the/?1 subtype, while both/I1 and 82 subtypes of receptors are present in glomeruli [8], data largely in agreement with our present results except for the lack of proximal 82 receptors. In contrast Healy et al have reported that those receptors distributing in glome~li are mainly of the pl subtype whilst the /I2 subtype of receptors are distributed in medullary tubules [22]. Although the reasons for the conflicting data reported in the literature, as well as some disagreements of our present results with others, may not be identified unequivocally, the problem of cross-reactivity of pharmacological agents should always be considered.…”
Section: Rt-pcr Of Intronless Genes Has Been Reported Bycontrasting
confidence: 96%
“…and Teitelbaum et al [15] who showed by using atenolol that /?-adrenergic receptors of subtype other than /I1 are present in cultured IMCD cells [15]), and from those studies it is not clear which subtype of receptors is invoived in most of the nephron segments. Using subtype-specific agents, two groups have reported the distribution of ,/31 and 82 subtypes of adrenergic receptors in the kidney by autoradiography [8,22], but their results are not totally in agreement with each other. Summers et al demonstrated that those receptors distributing in the distal nephron are mainly of the/?1 subtype, while both/I1 and 82 subtypes of receptors are present in glomeruli [8], data largely in agreement with our present results except for the lack of proximal 82 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, collecting tubules present in outer medulla mainly contained P2-adrenoceptors. These localizations of renal P-adrenoceptors are in general agreement with other reports (Summers & Kuhar, 1983;Summers et al, 1985;Healy et al, 1985). Surgical denervation did not alter the density of P-adrenoceptor subtypes present at cortical and outer medullary locations, implying that these receptors are not associated with renal sympathetic nerves innervating these structures (Barajas & Powers, 1990).…”
Section: Autoradiographysupporting
confidence: 91%
“…Renal βARs are involved in the modulation of both hemodynamics and electrolyte balance [167]. β 2 AR has been shown to regulate the expression of Na/Cl co-transporter expression, thereby participating in the development of salt sensitive hypertension [168,169].…”
Section: Introductionmentioning
confidence: 99%